The clinical analysis and treatment strategy of endovascular treatment for cerebral venous sinus thrombosis combined with intracerebral hemorrhage - Guo, Xin-bin; Liu, Shuo; Guan, Sheng (Scientific reports, 2020)
Cerebral venous sinus thrombosis (CVST) combined with intracerebral hemorrhage(ICH) is a special subgroup, and whether intrasinus thrombolysis (IST) or mechanical thrombectomy (MT) therapy should be carried out is controversial because of previous hemorrhage and possible delayed hemorrhage.The aim of this study was to analyze the safety and effectiveness of endovascular treatment of CVST with ICH and further discuss the treatment strategy. This is a retrospective study of 56 cases admitted from January 2010 to June 2019 diagnosed with CVST combined with ICH, and all were treated with endovascular treatment including IST with or without MT. We reviewed the clinical, radiological, and outcome data of all patients. The percentage of cases that showed complete and partial recanalization were 67.8% and 26.9% after endovascular treatment. ICH exacerbation occurred in 5 cases during thrombolysis. The percentage of cases with good outcome was 87.5% at discharge. 51 cases were followed up at sixth month. 49 cases had a mRS score of 0–2,and 2 cases had a mRS score of 3–4 at sixth month.Our data suggest that endovascular treatment may improve clinical and radiological outcome in most patients of CVST with ICH, but confirmation in prospective, controlled studies is warranted.